2020
DOI: 10.1111/dar.13171
|View full text |Cite
|
Sign up to set email alerts
|

Medical cannabis and cognitive performance in middle to old adults treated for chronic pain

Abstract: Introduction and Aims Cannabis exposure is becoming more common in older age but little is known about how it is associated with brain health in this population. This study assesses the relationship between long‐term medical cannabis (MC) use and cognitive function in a sample of middle‐aged and old chronic pain patients. Design and Methods A cross‐sectional study was conducted among chronic pain patients aged 50+ years who had MC licenses (n = 63) and a comparison group who did not have MC licenses (n = 62). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Fourteen other studies explicitly stated that all cannabis use, whether for medical or non-medical purposes, was evaluated [4, 97, 100, 104, 106, 108-110, 112, 116, 132, 135, 138, 144]. Fifteen NRSs focused strictly on medical use, overseen by a physician [94,98,99,101,111,120,121,131, PLOS ONE 133,136,148,149,152,156,158]; four focused strictly on non-prescribed medical use (i.e., taken for a perceived or actual medical condition, not for recreational purposes) [150,151,154,155]; and ten focused strictly on non-medical/recreational use [93,114,125,129,130,137,147,153,162]. The remaining NRS studied medical use of any kind [140].…”
Section: Interventions and Exposures Evaluated In The Included Primar...mentioning
confidence: 99%
“…Fourteen other studies explicitly stated that all cannabis use, whether for medical or non-medical purposes, was evaluated [4, 97, 100, 104, 106, 108-110, 112, 116, 132, 135, 138, 144]. Fifteen NRSs focused strictly on medical use, overseen by a physician [94,98,99,101,111,120,121,131, PLOS ONE 133,136,148,149,152,156,158]; four focused strictly on non-prescribed medical use (i.e., taken for a perceived or actual medical condition, not for recreational purposes) [150,151,154,155]; and ten focused strictly on non-medical/recreational use [93,114,125,129,130,137,147,153,162]. The remaining NRS studied medical use of any kind [140].…”
Section: Interventions and Exposures Evaluated In The Included Primar...mentioning
confidence: 99%
“…A recent review [ 50 ] reported two studies with a subject mean age over 65 which investigated cognitive function in cannabis users (current or former) and controls [ 51 , 52 ] and reported no difference in various cognitive measures. When cannabis use was stratified into THC and CBD groups, still no differences were seen in cognitive performance [ 53 ]. On the other hand, our study found significant differences only for the Flanker Test (FT-I and FT-E) between older THC users, CBD users, and NU, with THC users performing significantly worse than the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 An additional study examined cognitive performance among older adults with chronic pain, grouping participants by those who had a medical cannabis license and used regularly for at least 1 year and those without a license. 8 The researchers found no differences in cognitive performance between groups, though it is unclear to what extent those without a license had a history of cannabis use. These studies suggest that for older adults, relatively brief medical cannabis use may result in stabilized or improved cognitive performance through alleviating other factors impacting cognition (e.g., pain, sleep, mood), though the impacts of longer-term or recreational cannabis use on older adults' cognition remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Cognitive responses to cannabis use may vary based on life stage, as the development of the younger adult brain may be altered with cannabis use while older adults have completed development. 8 Furthermore, older adult cannabis users may face issues related to medical conditions, pharmacokinetics, or polypharmacy that can impact cognition but are less relevant to younger populations. 9,10 Gruber and colleagues examined the effects of cannabis use on cognition in a sample including older adult medical cannabis users, finding that 3 months of cannabis treatment led to improvements on measures of executive functioning as well as other measures of well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation